Crack development in steel-fibre-reinforced concrete members with conventional rebars. Issue 11 (26th April 2018) - Tiberti, Giuseppe; Trabucchi, Ivan; AlHamaydeh, Mohammad; Minelli, Fausto; Plizzari, Giovanni A.
Abstract : Although concrete performance has increased significantly over the last 20 years, the durability of concrete structures still remains a major concern. In fact, while concrete permeability has been remarkably reduced, aggressive agents can still penetrate concrete structures through cracks, which are generally present due to shrinkage or tensile stresses. A possible solution for crack control in structural members reinforced with conventional steel rebars is represented by fibre-reinforced concrete. In fact, fibre reinforcement improves the tension stiffening in the concrete portions between cracks and allows tensile stresses to be transmitted between the crack faces; both aspects reduce the crack distance and, as a consequence, the crack width. Within this framework, the aim of this paper is to shed new light on the crack control exhibited by steel-fibre-reinforced concrete (SFRC), having high post-cracking residual strength, in combination with steel rebars. In this regard, 32 tension ties under direct tension were tested. Special attention was devoted to the influence of the SFRC post-cracking performance on crack formation and development. The results confirmed a reduction in mean crack spacing compared with reinforced concrete members. However, beyond a nominal residual strength of around 5 MPa, no considerable reduction of the mean crack spacing was found.